Rancangan Pembelajaran Berkarakteristik Inovasi Abad 21pada Materi Teks Deskriptif Rumah Adat Jawamata Pelajaran Bahasa Jawa dengan Model Pembelajaran Cooperatif Learning di SMK Negeri 1 Dukuhturi Kabupaten Tegal - Didit Sutono (Universitas Pancasakti Tegal, 2022)
The cooperative learning model is one of the learning models that supports contextual learning. A cooperative teaching system can be defined as a group learning work system that is integrated. Based on the background above researchers will compare cooperatif learning models with text based instruction, discovery learning, and jigsaw types viewed from the perspective of 21st century learning innovation. Which of the three models is closest to the characteristics of learning abd 21 reviewed from the learning steps contained in the learning plan made by the teacher. With qualitative research, descriptive analysis is necessary. Descriptive analytical methods provide clear, objective, systematic, analytical and critical descriptions of educational values.